2019
DOI: 10.1093/jxb/erz350
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in the physiology and quality of fleshy fruits

Abstract: Fruits are unique to flowering plants and confer a selective advantage as they facilitate seed maturation and dispersal. In fleshy fruits, development and ripening are associated with numerous structural, biochemical, and physiological changes, including modifications in the general appearance, texture, flavor, and aroma, which ultimately convert the immature fruit into a considerably more attractive and palatable structure for seed dispersal by animals. Treatment with exogenous nitric oxide (NO) delays fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 124 publications
(115 reference statements)
2
61
0
Order By: Relevance
“…NO promotes leaf expansion, represses floral transition, stimulates light-dependent germination, promotes de-etiolation, inhibits maturation, and senescence, ( Bruand and Meilhoc, 2019 ). Like in pepper, tomato, strawberry, and avocado plants ( Gonzalez-Gordo et al., 2019 ; Palma et al., 2019 ), the present work indicated that the release of NO progressively declined during fruit ripening in Lycium plants, a medicinal and edible species. These results may show that it is a conserved event for endogenous NO production decline during fresh fruit ripening.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…NO promotes leaf expansion, represses floral transition, stimulates light-dependent germination, promotes de-etiolation, inhibits maturation, and senescence, ( Bruand and Meilhoc, 2019 ). Like in pepper, tomato, strawberry, and avocado plants ( Gonzalez-Gordo et al., 2019 ; Palma et al., 2019 ), the present work indicated that the release of NO progressively declined during fruit ripening in Lycium plants, a medicinal and edible species. These results may show that it is a conserved event for endogenous NO production decline during fresh fruit ripening.…”
Section: Discussionsupporting
confidence: 57%
“…These results may show that it is a conserved event for endogenous NO production decline during fresh fruit ripening. In other words, NO has been demonstrated to delay fruit ripening generally, independently on whether fruits are climacteric or nonclimacteric ( Palma et al., 2019 ). Integrating the results that the LbNR transcript amount is significantly positively correlated with the NO release during fruit ripening and that the VIGS-mediated LbNR gene silencing significantly decreased the NO production in ripe Lycium fruits, we could conclude that NR was partially responsible for NO biosynthesis in Lycium plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excepting Alegría which has been scarcely used for research purposes, reports on the other three varieties can be found in the literature. Thus, Melchor variety has been used to decipher the mechanisms involved in fruit ripening [18,39,66,67] where some of their antioxidant system have been reported to be involved [68]. Variety Piquillo was used as model to address the effects triggered by infection with Verticillum [69][70][71][72] and how to protect pepper plants against it through diverse practices [73,74], as well as to investigate the effect of sanitized sewage sludge on the growth, yield, fruit quality, soil microbial community and the physiology of pepper plants [75,76].…”
Section: The Experimental Design Provided a Gradual Capsaicin Concentmentioning
confidence: 99%